(untitled) (Architecture Image Studies, 2025)
This study explores the concept of mitigating circumstances in Jordanian legislation, with a particular focus on cybercrime. Mitigation is presented as a key mechanism for achieving individualized justice and ensuring proportionality between crime and punishment. It does not eliminate criminal responsibility but influences the severity or type of penalty imposed. The research finds that while the Jordanian legislator acknowledged mitigation in cybercrime, its application was narrowly confined to Article 29 of the Cybercrime Law, drafted in a limited and ambiguous manner. This undermined the legislative aim of encouraging offender cooperation with authorities. In contrast, the Penal Code provides broader grounds for mitigation, whether through statutory excuses or judicial discretion. Although this flexibility enhances fairness, it also risks inconsistency in judicial practice due to the absence of unified standards. The study concludes that Jordan’s criminal policy requires reform, particularly by clarifying cybercrime provisions and establishing coherent criteria for judicial discretion.